Pengembangan Wisata Lokal Berbasis Sosial Ekonomi untuk Menwujudkan Desa Berdaya Saing dan Berkelanjutan - Atmojo, Muhammad Eko; Dian Fridayani, Helen; Perdana, Vicky Alfitra (Civiliza Publishing, 2024)
Village development is an important thing to do as mandated by Law Number 6 of 2014 concerning Villages. Semoyo Village formed Agromoyo Sejahtera as part of the village development efforts focused on the tourism economy. This institution was formed to accommodate the potential of Semoyo Village so that it can become a source of development that has an impact on the welfare of the local community. However, because the institution is still new, there are quite a number of problems that surround it. The problems of Agromoyo Sejahtera include institutional and product development including marketing. These problems certainly need to be resolved immediately so that Agromoyo Sejahtera can maximise the space for movement in managing existing local potential. For this reason, the proposing team has an activity plan that is offered as an alternative form of problem solving solution for this institution. The solutions are structural development of Argomoyo Sejahtera management institutions, branding and tourism marketing assistance, and legal assistance for tourism business